TRACING OF COVID-19 TRANSMISSION BASED ON CLOSE CONTACT POPULATION: CASES IN SOUTH SUMATRA: Penelusuran penularan COVID-19 dari Populasi Kontak Erat: Kasus di Sumatera Selatan - Rico Januar Sitorus; Hariadi Wibisono; Hibsah Ridwan; Nyoman Yudi Antara; Merry Natalia Panjaitan; Reymart V. Sangalang (Jurnal Berkala Epidemiologi, 2023)
Background: COVID-19 causes a high death toll, illness, and economic losses. Transmission of the virus occurs from human to human and has spread to more than 200 countries. The purpose of this research is to determine the relationship between close contact and the COVID-19 incident in South Sumatra, Indonesia. Methods: This research used an observational analysis with a cross-sectional design. The population in this study was all COVID-19 patients and those who had close contact with COVID-19 patients in South Sumatra. The data were analyzed using univariate, bivariate, and multivariate tests. The bivariate analysis uses the chi-square test, while the multivariate analysis uses the logistic regression test. Results: The results show that close contact was related to the incidence of COVID-19 with a P value of 0.00 and an odds ratio adjusted (ORAdj) of 3.59 (95% CI: 2.93–4.39) after the variables of record of visiting local transmission areas, record of visiting health facilities, record of contact with suspected cases, and record of contact with confirmed cases were controlled. Conclusion: The transmission of close contact within families such as households was very high. A transmission could occur between a husband and wife and people who lived in the same house and shared plates while eating. To prevent a broader transmission, people who had close contact with COVID-19 needed to be quarantined. We could carry out public health interventions globally to fight against the pandemic based on these results.